Influence of TiO2 nanoparticles on the optical and structural properties of PPV thin films converted at low temperatures - B. Rostirolla; E. Laureto; M. A. T. da Silva; H. de Santana; I. F. L. Dias; J. L. Duarte (eXPRESS Polymer Letters, 2013)
In this work we studied the optical properties of poly(p-phenylene vinylene) (PPV) produced by the thermal conversion of a precursor polymer blended with a synthetic dye (Reactive Black 5). The production of PPV by this method decreases the overall time and cost of the process. We observed that the introduction of the dye resulted in an additional absorbance band near 550–700 nm, which can be beneficial to the photon harvesting capacity of the polymer if it is used as the donor material in a photovoltaic device. We studied how the optical and structures properties of this blend change when different quantities of TiO2 nanoparticles are introduced. For that, thin films were produced by the cast deposition of pre-PPV:dye:TiO2. The scanning electronic microscopic images showed that the inorganic semiconductor form large agglomerates of approximately 200 nm, indicating a very rough surface where the dye can be adsorbed. The analysis of photoluminescence and Raman peaks indicated a reduction of the mean conjugation length of the polymer chains in the presence of TiO2 nanoparticles.